A preliminary survey of the milpa system of maize culture as practiced by the Maya indiand of the Northern part of the Yucatan Peninsula - Emerson, R.A.
In January and Febrary of 1915, Profesor R.A. Emerson, of Cornell University, and Mr. J. H. Kepton, then of the U.S. Departament of Agriculture, studied maize farming among the Maya Indians at the request of the Carnegie Institution. The following report, circulated in mimeographed form under Dr. Emerson's name, is one of the tangible results of this preliminary survey.
Keywords: AGRICULTURA-MAYAS; MAIZ; MAIZ-MAYAS